(untitled) - Klimchuk, Marianne Rosner (Hoboken, New Jersey, 2012)
Now in full-color throughout, the second edition of Packaging Design offers fully up-to-date coverage of the entire packaging design process, including the business of packaging design, design principles, the creative process, and pre-production and production issues. New chapters cover topics related to branding, business strategies, social responsibility, and sustainability. All new case studies and examples illustrate every phase of the process, making this the single most important guide for designers on how to create successful packaging designs that serve as the marketing vehicle for consumer products
Keywords: Packaging,Bao bì; Design,Thiết kế